2016
DOI: 10.1007/s00449-016-1586-9
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of staged bioleaching of low-grade chalcopyrite ore in the presence and absence of chloride in the irrigating lixiviant: ANFIS simulation

Abstract: In this investigation, copper was bioleached from a low-grade chalcopyrite ore using a chloride-containing lixiviant. In this regard, firstly, the composition of the bacterial culture media was designed to control the cost in commercial application. The bacterial culture used in this process was acclimated to the presence of chloride in the lixiviant. Practically speaking, the modified culture helped the bio-heap-leaching system operate in the chloridic media. Compared to the copper recovery from the low-grade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Several methods have been used to increase reaction rates and break or avoid this passivation layer in leaching systems, including (i) leaching with powerful oxidizing agents such as O 3 [ 30 , 31 , 32 ], H 2 O 2 [ 6 , 33 , 34 , 35 ], potassium permanganate, and potassium dichromate [ 36 , 37 , 38 ], (ii) leaching with high pressure and temperature [ 34 , 39 , 40 , 41 ], and (iii) bacterial leaching [ 11 , 14 , 42 , 43 ], but these improvements are accompanied by limitations, mainly due to the high cost of oxidizers, the corrosive environments they provide and even low copper recoveries [ 39 , 44 ]. These kinds of considerations result in the hydrometallurgical route not being widely used in the dissolution of copper from primary sulfide ore, mainly because of slow leaching kinetics caused by the crystal structure of chalcopyrite (face-centered tetragonal lattice), which makes its lattice energy too high to break S-Cu-Fe bonds [ 23 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been used to increase reaction rates and break or avoid this passivation layer in leaching systems, including (i) leaching with powerful oxidizing agents such as O 3 [ 30 , 31 , 32 ], H 2 O 2 [ 6 , 33 , 34 , 35 ], potassium permanganate, and potassium dichromate [ 36 , 37 , 38 ], (ii) leaching with high pressure and temperature [ 34 , 39 , 40 , 41 ], and (iii) bacterial leaching [ 11 , 14 , 42 , 43 ], but these improvements are accompanied by limitations, mainly due to the high cost of oxidizers, the corrosive environments they provide and even low copper recoveries [ 39 , 44 ]. These kinds of considerations result in the hydrometallurgical route not being widely used in the dissolution of copper from primary sulfide ore, mainly because of slow leaching kinetics caused by the crystal structure of chalcopyrite (face-centered tetragonal lattice), which makes its lattice energy too high to break S-Cu-Fe bonds [ 23 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chalcopyrite (CuFeS2) is the main source of copper, and about 70% of the world's copper produces from porphyry copper deposits (Wang, 2005) that full-scale hydrometallurgical processes are under developments so far (Petersen, 2016;Vakylabad et al, 2016). A wide variety of hydrometallurgical methods have been considered to address issues involved in the leaching of chalcopyrite-bearing ore types.…”
Section: Introductionmentioning
confidence: 99%
“…A wide variety of hydrometallurgical methods have been considered to address issues involved in the leaching of chalcopyrite-bearing ore types. For example, bioleaching (Vakylabad et al, 2016), pressure-leaching (Li et al, 2018), and Galvanox™ (Dixon et al, 2008) processes are widely reported in the literature. The first industrially commercial application was high-temperature and pressure leaching of Phelps-Dodge process (Marsden et al, 2003) developed at Bagdad, Arizona, U.S.A, in 2003.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Underground Development of Mineral Subsoil Using Microorganisms: A Mini-Review Computational Fluid Dynamics (CDF-Simulation) [23], ANN modeling (Artifi cial Neural Network Modeling) [24], or ANFIS-simulation [25] can be used for this purpose. Th e last of these approaches is the most progressive, accurate, and highly productive way of modeling, but it brings to a unifi ed industrial level suitable for all possible scenarios of bacterial leaching processes and requires further improvement of analytical algorithms.…”
mentioning
confidence: 99%